Investigation of airflow onto uncooled and cooled perpendicular substrates for bioaerosol sampling. Issue 3 (4th March 2023) - Song, Zhixiong; Abid, Hassan Ali; Lin, Eric Shen; Ong, Jian Wern; Uddin, Md. Hemayet; Margo, Kenneth; Liew, Oi Wah; Ng, Tuck Wah
Abstract: A better understanding of the mechanics of condensation is needed to devise active bioaerosol samplers. Here, dropwise water condensation produced by directing humid air flow perpendicularly on ambient (25 °C) and cooled (4 °C) copper plate substrates was studied. Numerical data obtained from solving the two-dimensional incompressible Navier–Stokes equations with low Reynolds numbers (=40) showed significant vorticity strength developing at the edges of the copper plate. This resulted in a higher degree of aerosol deposition and an increased likelihood of drop nucleation at the impaction zone. When a drop is already present at the edge, simulations predicted that the high vorticity region shifted to the apexes of drops with concomitant increase in the magnitude of vorticity strength. These results explained the experimentally observed dropwise condensation of larger drops at the edges of the ambient substrate. Analyses of drop size distributions at the center and edges of ambient and cooled substrates showed that drop growth was enhanced by improved condensation on the cooled substrate surface in addition to the flow vorticity effect. Preliminary findings indicate that the recovery of viable aerosolized Escherichia coli from ambient and cooled substrate was found to be invariant, portending its utility for sampling when the electrical power available for cooling is limited. Copyright © 2023 American Association for Aerosol Research